2005
DOI: 10.1038/nature03245
|View full text |Cite
|
Sign up to set email alerts
|

The mass of the missing baryons in the X-ray forest of the warm–hot intergalactic medium

Abstract: Recent cosmological measurements indicate that baryons comprise about four per cent of the total mass-energy density of the Universe, which is in accord with the predictions arising from studies of the production of the lightest elements. It is also in agreement with the actual number of baryons detected at early times (redshifts z > 2). Close to our own epoch (z < 2), however, the number of baryons detected add up to just over half (approximately 55 per cent) of the number seen at z > 2 (refs 6-11), meaning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
185
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(193 citation statements)
references
References 24 publications
6
185
1
Order By: Relevance
“…In the cosmic baryon budget, it is now well known that only about 6% of them shine as stars and gas in galaxies (Fukugita et al 1998). Locally, UV absorption in front of background sources have shown that as much as 30% of baryons could be associated with the Lymanα forest and an uncertain fraction (5−10%) with the warm-hot medium (WHIM at 10 5 −10 6 K, Nicastro et al 2005;Danforth et al 2006). So about half of the baryons are not yet accounted for.…”
Section: Introductionmentioning
confidence: 99%
“…In the cosmic baryon budget, it is now well known that only about 6% of them shine as stars and gas in galaxies (Fukugita et al 1998). Locally, UV absorption in front of background sources have shown that as much as 30% of baryons could be associated with the Lymanα forest and an uncertain fraction (5−10%) with the warm-hot medium (WHIM at 10 5 −10 6 K, Nicastro et al 2005;Danforth et al 2006). So about half of the baryons are not yet accounted for.…”
Section: Introductionmentioning
confidence: 99%
“…If so, important objectives are (1) to investigate the intergalactic magnetic field strength and structure, (2) to determine the excitation state and metallicity of any associated warm-hot intergalactic medium (WHIM; e.g., Henry 2004;Nicastro et al 2005), (3) to understand the intergalactic cosmic-ray spectrum (e.g., , and (4) to define the propagation environment of ultraYhigh-energy cosmic rays (UHECRs; e.g., Sigl et al 2004). The achievement of these goals is ultimately important for solving important puzzles in high-energy astrophysics, astroparticle physics, the origin of cosmic magnetic fields, and the evolution of LSS.…”
Section: Introductionmentioning
confidence: 99%
“…19, this issue) must be used at their sensitivity limits and the most plausible detections (e.g. Nicastro et al 2005) are indeed still debated (Kaastra et al 2006). Firm detections are however of great relevance, because the existence of the WHIM and the estimate of its properties would be an extraordinary confirmation of the current model of structure formation.…”
Section: The Surrounding Whimmentioning
confidence: 99%